The Suitability of Physical Elements and Visual Landscape Aesthetics in Mataram City Parks: A Scenic Beauty Estimation Approach - Rafif, Tegar Djulfiqar; Valentino, Niechi; Prasetyo, Andrie Ridzki (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
its vision of a harmonious, safe, welcoming, outstanding, and self-reliant city. The utilization of Green Open Spaces (GOS) plays a crucial role in improving quality of life, supporting environmental sustainability, fostering social interaction, and providing support for small and medium-sized enterprises to grow. This study aims to: 1) analyze the suitability of these spaces based on the principles of a sustainable city at Mayura Park, Udayana Park, and Sangkareang Park; 2) analyze the aesthetic quality of Mayura Park, Udayana Park, and Sangkareang Park. Using a deductive approach with quantitative research methods, this study examined Mayura, Udayana, and Sangkareang Parks as samples of Mataram’s urban parks and found that elements such as vegetation, biodiversity, microclimate, activity variety, sociocultural facilities, accessibility, and nature-based tourism activities align with the concept of sustainable cities. However, aspects related to water management, the utilization of renewable resources, cultural identity, comfort, safety, cleanliness, and economic activities still do not meet the expected criteria. Mayura and Sangkareang Parks demonstrate a moderate level of compliance, while Udayana Park exhibits a high level of compliance. Overall, the suitability of Mataram’s urban parks is still considered moderate, so efforts are needed to improve their quality so that Mataram can become a sustainable, welcoming, and inclusive city.